COMPREHENSIVE TRANSACTIVE ENERGY MANAGEMENT SYSTEMS - Zhambyl, Aidyn (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Traditional power systems based on the generation of power from conventional energy sources, e.g., coal, oil, and/or gas. The use of these sources for power generation leads to greenhouse gas emission issues. Hence, in order to reduce the level of emissions, the use of renewable energy sources is highly recommended. Modern power grids must be smart and therefore, must be adaptable to the current needs of users. In other words, the system must be sustainable to the infinitely changing power demands. The main objective of this work is to develop the model that decomposes DLMP into components and determines price signals in terms of active and reactive power cost, congestion cost, power losses cost, voltage cost. This approach can help to identify energy services provided by local participants and therefore, evaluate their contributions.
Keywords: Research Subject Categories::TECHNOLOGY; Type of access: Gated Access; Distributed Energy Storage Systems; Optimal Power Flow; Transactive Energy Market